Differentiation of transforming growth factor Î²1-induced mesenchymal stem cells into nucleus pulposus-like cells under simulated microgravity conditions - Han, C; Jiang, C; Yu, C; Shen, H (Cellular and Molecular Biology, 2015)
This study aims to observe the differentiation effects of transforming growth factor Î²1 (TGF-Î²1)-transfected bone marrow mesenchymal stem cells (BMMSCs) into the nucleus pulposus-like cells under simulated microgravity conditions. BMMSCs were isolated from the adult rabbits, then cultured and proliferated to the third generation. After transfected by TGF-Î²1, these MMSCs were incubated in the calcium alginate gel microspheres and rotary cell culture system. The content changes of TGF-Î²1 inside BMMSCs, as well as the proliferation abilities of BMMSCs, were detected. The immunohistochemistry and toluidine blue staining were performed to detect the type II collagen. The RT-PCR method was performed to detect the expressions of proteoglycan and type II collagen mRNA. Results found that, on the 14th day, the polygonal nucleus pulposus-like cells could be observed. The TGF-Î²1 content inside the supernatant and the DNA content inside BMMSCs were significantly increased (P<0.05). The immunohistochemistry staining exhibited the positive results about the type II collagen. RT-PCR showed the expressions of proteoglycan and type II collagen mRNA inside BMMSCs. The TGF-Î²1-transfected BMSCs exhibited the increased synthesizing abilities of proteoglycan and type II collagen under simulated microgravity conditions than the control group.